Pengaruh Berbagai Jenis Pupuk Kandang Terhadap Pertumbuhan Dan Hasil Tanaman Bunga Kol (Brassica olerancea var. botrytis L.) Varietas PM 126 F1 - Purnama, Vera; Lusiana, Lusiana; Racman, Fajar (OrchidAgro, 2024)
The research aims to determine the best types of manure for the growth and yield of flower plants (Brassica olerencea var. botrytis L.) PM 126 F1 variety. The research was carried out in Palabuan Hamlet, Sukamelang Village, Subang District, Subang Regency with an altitude of 50 meters above sea level, the research started from June to August 2023. The research was carried out using a Randomized Block Design (RAK) with 8 treatments of various types of manure (Manure). chicken 15 tons/ha, chicken manure 25 tons/ha, cow drum fertilizer 15 tons/ha, cow manure 25 tons/ha, goat manure 15 tons/ha, goat drum fertilizer 25 tons/ha, bat guano manure 15 tons/ha, fertilizer bat guano cages 25 tons/ha) repeated 3 times with a total of 24 plots. The research results showed that various types of manure had an effect on the observation parameters of plant height at 21 HST and 28 HST, leaf area, plant dry weight, flower weight, and flower diameter. Cow manure at a dose of 25 tons/ha produced the best cauliflower weight, namely 207.73 grams.Â Â